2003
DOI: 10.1101/gr.910003
|View full text |Cite
|
Sign up to set email alerts
|

EST Mining and Functional Expression Assays Identify Extracellular Effector Proteins From the Plant PathogenPhytophthora

Abstract: Plant pathogenic microbes have the remarkable ability to manipulate biochemical, physiological, and morphological processes in their host plants. These manipulations are achieved through a diverse array of effector molecules that can either promote infection or trigger defense responses. We describe a general functional genomics approach aimed at identifying extracellular effector proteins from plant pathogenic microorganisms by combining data mining of expressed sequence tags (ESTs) with virus-based high-thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
356
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(368 citation statements)
references
References 58 publications
8
356
0
Order By: Relevance
“…Normally, expanding cell death can be found at the sites about two weeks after tooth-pick inoculation. As shown in both figure panels, expanding cell death is present at the sites that were tooth-pick inoculated with pGR106-CRN2 (positive control using the effector crinkler Crn2), which is a general cell death inducing gene from P. infestans 27 . Apart from minor response to wounding, no expanding cell death is noted at the sites that were tooth-pick inoculated with the pGR106-empty (negative control).…”
Section: Scoringmentioning
confidence: 99%
“…Normally, expanding cell death can be found at the sites about two weeks after tooth-pick inoculation. As shown in both figure panels, expanding cell death is present at the sites that were tooth-pick inoculated with pGR106-CRN2 (positive control using the effector crinkler Crn2), which is a general cell death inducing gene from P. infestans 27 . Apart from minor response to wounding, no expanding cell death is noted at the sites that were tooth-pick inoculated with the pGR106-empty (negative control).…”
Section: Scoringmentioning
confidence: 99%
“…ORFs encoding putative RXLR sequences Kamoun 2006;Rehmany et al, 2005) were identified using the combined procedures outlined by Bhattacharjee et al (2006) and Torto et al (2003). A total of 159 ORFs putatively encoding secreted RXLR proteins were identified on the 135 supercontig sequences containing matches to Pinci1.…”
Section: Genomic Distribution Of Pinci1 In Relation To Other Expressementioning
confidence: 99%
“…Since each of these avirulence proteins appears to enter the host cells, they have been inferred to be effector proteins. Several fungal and oomycete effector proteins that are not associated with resistance gene interactions have also been shown or inferred to enter plant cells, including Phytophthora elicitin (Tyler, 2002) and crinkler (Torto et al, 2003) proteins, the RTP1p protein of the bean rust Uromyces fabae (Kemen et al, 2005), and the ToxA protein toxin of Pyrenophora tritici-repentis (Manning and Ciuffetti, 2005). In all cases, the mechanisms by which these proteins might enter the cell are unknown.…”
Section: Introductionmentioning
confidence: 99%